Training on Making Shibori Products for Students at SLB Widya Shantika - Bela Prawisma; Fajar Khoiriyah; Fatima Bunga Imani; Hada Karunia Fitrah; Irsyad Ammatullah; Yuniar Rizkia Arumdhani; Ediyanto Ediyanto (Jurnal Pengabdian Masyarakat Bestari, 2023)
Shibori is a cloth decoration technique that is done by tying, folding, or making cloth knots. Interesting motifs and have a high selling value. Training is one way that can be used to increase community creativity. This community service research method is descriptive qualitative. Data collection techniques were carried out through field notes, documentation, and observation. Data analysis is collected based on certain groups. The shibori-making training consists of two stages, namely 1) providing general information; and 2) theoretical and practical activities. The response of students with special needs and the school showed very good results. After the training, new knowledge and insight emerged for students with special needs and fine motor skills also increased, as evidenced by the regular mixing of motif colors.